PSYCHOLOGICAL SELF-DEFENSE AS A MARKER OF INDIVIDUAL PROTECTIVE STYLE (Psychology Travelogs, 2023)
The article defines the place of psychological self-defense in the structure of the individual protective style of personality. In particular, it is noted that real defensive behavior is a single system of different in nature and function defensive components that form an individual defensive style of personality. The defensive style is integrated into more global personality structures and can be described through parameters that are not defensive in nature, but reflect integrative personality properties. The interconnectedness of the parameters forms stable patterns that determine the general configuration of a person's defensive behavior and form the integrity of his or her individual defensive style. There are the following patterns: the pattern of "sociality" - implements the adaptive function of psychological self-defense in the field of social adaptation; the pattern of "supersituationality" - determines the tendency to "protective search" and may be associated with the experience of personal development crises; the pattern of "inclusion" - "non-inclusion" - reflects an active or, conversely, passive attitude to the external situation. In this case, inclusion implies an active perception of the situation - a quick response, deep study of the problem situation and further integration of new experience into the world picture. Non-inclusion is characterized by a tendency to ignore the problematic situation, not respond to many external signals and make the same type of mistakes; the "opportunity search" pattern is responsible for adaptation in terms of using the opportunities of the situation. The data obtained allow us to supplement the idea of the place of psychological self-defense in the structure of personality. Patterns of individual protective style illustrate the possibility of defensive behavior going beyond reactivity and its integration into teleological characteristics of the individual.
Keywords: psychological self-defense; individual protective style; personality; personal properties; patterns